A systematic review of teacher-facing dashboards for collaborative learning activities and tools in online higher education - Romão, Tiago (2023)
Dashboard for online higher education support monitoring and evaluation of students’ interactions, but mostly limited to interaction occurring within learning management systems. In this study, we sought to find which collaborative learning activities and tools in online higher education are included in teaching dashboards. By following Kitchenham’s procedure for systematic reviews, 36 papers were identified according to this focus and analysed. The results identify dashboards supporting collaborative tools, both synchronous and asynchronous, along categories such as learning management systems, communication tools, social media, computer programming code management platforms, project management platforms, and collaborative writing tools. Dashboard support was also found for collaborative activities, grouped under four categories of forum discussion activities, three categories of communication activities and four categories of collaborative editing/sharing activities, though most of the analysed dashboards only provide support for no more than two or three collaborative tools. This represents a need for further research on how to develop dashboards that combine data from a more diverse set of collaborative activities and tools.